2002
DOI: 10.1097/00000539-200208000-00046
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Responses to Tracheal Intubation with Laryngoscope Versus Lightwand Intubating Device (Trachlight®) in Adults with Normal Airway

Abstract: The magnitude of hemodynamic changes associated with tracheal intubation with the Trachlight is almost the same as that which occurs with the direct laryngoscope. Hemodynamic changes are likely to occur because of direct tracheal irritation rather than direct stimulation of the larynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 13 publications
4
50
1
Order By: Relevance
“…The results of the present and other studies, [8][9][10][11] however, suggest that the circulatory response to EI is mainly due to stimulation of the trachea by the endotracheal tube rather than stimulation of the glottis by the laryngoscope. Furthermore, one of the studies mentioned 9 suggested that, in the lightwand intubation technique, grasping of the jaw and lifting it upward to make a clear passage for the endotracheal tube to enter the glottic opening was sufficient to cause a circulatory response similar to that found with conventional laryngoscopy.…”
Section: Me Et Th Ho Od Ds Scontrasting
confidence: 64%
See 1 more Smart Citation
“…The results of the present and other studies, [8][9][10][11] however, suggest that the circulatory response to EI is mainly due to stimulation of the trachea by the endotracheal tube rather than stimulation of the glottis by the laryngoscope. Furthermore, one of the studies mentioned 9 suggested that, in the lightwand intubation technique, grasping of the jaw and lifting it upward to make a clear passage for the endotracheal tube to enter the glottic opening was sufficient to cause a circulatory response similar to that found with conventional laryngoscopy.…”
Section: Me Et Th Ho Od Ds Scontrasting
confidence: 64%
“…A study comparing two direct laryngoscope blades, the Macintosh 3, and the Miller 2, with lighted stylet intubation showed no significant difference in hemodynamic changes among the three groups. 7 More recently, Casati et al, 8 Hirabayasi et al, 9 Friedman et al 10 and Takahashi et al 11 have studied the effects of lightwand technique on circulatory responses to tracheal intubation in adult patients: no differences between the lightwand technique and direct-vision laryngoscopy in changes in arterial pressure and HR, during and after EI, were found, while the time taken to achieve tracheal intubation was comparable. These studies were conducted in American Society of Anesthesiologists physical status I and II patients.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 96%
“…A study comparing the lightwand and the Macintosh laryngoscope reported attenuation of the haemodynamic response to tracheal intubation with the lightwand in normotensive patients, but not in hypertensive patients [19], while another study reported the opposite result [20]. However, there are many studies comparing the lightwand and Macintosh laryngoscope in which no difference in haemodynamic response was observed [21][22][23]. Montes et al concluded that direct stimulation of the trachea is a major cause of the haemodynamic changes associated with tracheal intubation [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many studies comparing the lightwand and Macintosh laryngoscope in which no difference in haemodynamic response was observed [21][22][23]. Montes et al concluded that direct stimulation of the trachea is a major cause of the haemodynamic changes associated with tracheal intubation [22]. On the other hand, a number of studies investigating the Airtraq reported fewer changes in blood pressure and heart rate compared with Macintosh laryngoscopy [1,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the shape of the stylet may hinder its removal and cause longer intubation times. In addition, a recent study showed that intubation times with video laryngoscopes can be decreased with proper preparation of the stylet and tracheal tube (7,27 Various studies indicated that laryngoscopy may cause an undesirable increase in blood pressure and heart rate in anesthetized patients (29)(30)(31)(32)(33)(34)(35). Various video laryngoscopes have been studied to elucidate the hemodynamic changes during orotracheal intubation; however, there has been no study comparing the hemodynamic response to orotracheal intubation of the McGrath Series 5 video laryngoscope and the Macintosh laryngoscope (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%